2008
DOI: 10.1101/lm.726008
|View full text |Cite
|
Sign up to set email alerts
|

Sustained increase in hippocampal sharp-wave ripple activity during slow-wave sleep after learning

Abstract: High-frequency oscillations, known as sharp-wave/ripple (SPW-R) complexes occurring in hippocampus during slow-wave sleep (SWS), have been proposed to promote synaptic plasticity necessary for memory consolidation. We recorded sleep for 3 h after rats were trained on an odor-reward association task. Learning resulted in an increased number SPW-Rs during the first hour of post-learning SWS. The magnitude of ripple events and their duration were also elevated for up to 2 h after the newly formed memory. Rats tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
164
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(199 citation statements)
references
References 46 publications
26
164
1
3
Order By: Relevance
“…These properties have been specified at a theoretical level in McClelland et al (1995), have been modelled in Alvarez and Squire (1994), and can be summarised as follows (cf. Rolls and Kesner, 2006): (a) Hip has important reciprocal connections with many associative cortical areas (e.g., PFC, IT, PPC) and sub-cortical nuclei (e.g., NAcc and Amg); (b) Hip neurons have massive lateral connectivity; (c) Hip is one of the brain loci where rapid associative learning leading to Long Term Potentiation is strongly present; (d) Hip has been shown to reactivate during sleeping (McClelland et al, 1995;Eschenko et al, 2008).…”
Section: Affective Labelingmentioning
confidence: 99%
“…These properties have been specified at a theoretical level in McClelland et al (1995), have been modelled in Alvarez and Squire (1994), and can be summarised as follows (cf. Rolls and Kesner, 2006): (a) Hip has important reciprocal connections with many associative cortical areas (e.g., PFC, IT, PPC) and sub-cortical nuclei (e.g., NAcc and Amg); (b) Hip neurons have massive lateral connectivity; (c) Hip is one of the brain loci where rapid associative learning leading to Long Term Potentiation is strongly present; (d) Hip has been shown to reactivate during sleeping (McClelland et al, 1995;Eschenko et al, 2008).…”
Section: Affective Labelingmentioning
confidence: 99%
“…A training-induced increase in ripple rate (Eschenko et al, 2008) has been found previously when recordings were made in rats following a spatial learning task, over a longer period of time, during sleep. These differences in methods probably account at least partially for the different results, i.e., the absence of an increase in postsession ripple rate in the ripple-contingent group obtained in our study.…”
mentioning
confidence: 90%
“…Next a negative threshold of M Ϫ 7 ϫ SD was set for each 5 min period of each animal. The number of ripples per minute and then the change (percentage) in the number of ripples per minute from presession to postsession recordings was calculated (Eschenko et al, 2008).…”
Section: Recordings and Data Analysismentioning
confidence: 99%
“…Highfrequency oscillations-known as sharp-wave/ripple / / (SPW-R) complexes and occurring during NREM-have an important role in neuronal communication and synaptic plasticity and promote memory consolidation (Jensen, Kaiser, & Lachaux, 2007). A recent study found that learning resulted in an increased number of SPW-Rs during the first hour of postlearning NREM sleep (Eschenko, Ramadan, Mölle, Born, & Sara, 2008). Therefore, there is the possibility that part of the memory consolidation damage induced by the MMPM may be related to the decrease in the amount of NREM sleep.…”
Section: Rem Sleep Deprivation (Mmpm)mentioning
confidence: 99%